Barriers and facilitators to maintaining a high level of polypharmacy adherence in people living with HIV: A scoping review - He, Jiamin; Zhu, Zheng; Sun, Meiyan; Liu, Xiaoning; Yu, Junwen; Zhang, Lin; Lu, Hongzhou (Frontiers in Pharmacology, 2023)
Objectives: With the prolongation of life span and increasing incidence of comorbidities, polypharmacy has become a challenge for people living with HIV (PLWH). This review aims to identify barriers and facilitators to maintaining a high level of polypharmacy adherence in PLWH. Methods: Nine electronic databases were searched for studies from 1996 to October 2021. Studies were included if they were conducted in adult PLWH and reported barriers and facilitators to maintaining a high level of polypharmacy adherence. This review presents a conceptual framework model to help understand the barriers and facilitators. Results: Twenty-nine studies were included. The majority of publications were observational studies. Eighty specific factors were identified and further divided into five categories, including individual factors, treatment-related factors, condition-related factors, healthcare provider-related factors, and socioeconomic factors, based on the multidimensional adherence model (MAM). Conclusions: Eighty factors associated with polypharmacy adherence among PLWH were identified and grouped into five major categories. Healthcare providers can make decisions based on the five categories of relevant factors described in this paper when developing interventions to enhance polypharmacy adherence. It is recommended that medications be evaluated separately and that an overall medication evaluation be conducted at the same time to prevent inappropriate polypharmacy use.